Synthesis of polyquaternium-functionalized hydrochar for adsorptive removal of methyl orange and diclofenac sodium - Lei Cui; Kun Ye; Hao-Yang He; Bing Li (Journal of Water Process Engineering, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Engineering lignin-incorporated hydrogels for agricultural and environmental applications: From synthesis to sustainable implementation - Fuke Ai; Xiaolei Zhang; Bing Hu; Shin Ying Foong; Weidong Ye; Yameng Li; Quanguo Zhang; Pedram Fatehi; Siming You; Zhiping Zhang (Bioresource Technology, 2026)

Topographic slope preference of ferromanganese nodules in the Eastern Pacific: A dual-scale bathymetric analysis - Jixin Wang; Xiangwen Ren; Shijuan Yan; Bing Li; Jun Ye; Li Chuanshun; Xuefa Shi; Dewen Du (Marine Georesources & Geotechnology, 2026)

Linking botany and mineral exploration: Alhagi sparsifolia as a potential indicator for Ni-Cu sulfide deposits - Meng-Meng Cui; Ben-Xun Su; Shan-Ke Liu; Hui-Li Yan; Wen-Jun Li; Bing-Yu Gao; Jing Wang; Zhen-Yan He; Shu-Kuan Wu; Ye-Tao Tang (Journal of Asian Earth Sciences, 2026)

Humic acid-mediated biomineralization of high-purity struvite from copper-containing wastewater for phosphorus recovery - Ye Wang; Hanbing Li; Bing Li; Xiaoxiong Wang; Wei Yu; Shungui Zhou; Yuefei Huang (Chemical Engineering Journal, 2026)

Retraction notice to “Determining the spatial non-stationarity underlying social and natural environment in thyroid cancer in China” [Sci. Total Environ. 870 (2023) 162009] - Xiyu Zhang; Yongqiang Lai; Xiaodan Bai; Bing Wu; Wenjing Xiang; Chenxi Zhang; Guihong Geng; Wenqing Miao; Qi Xia; Qunhong Wu; Huiying Yang; Yanjie Wang; et al. (Science of The Total Environment, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

A coherent feature representation based gated recurrent unit network for underwater acoustic target recognition - Jia Xu; Haijun Liu; Qingkai Hou; Ye Zhang; Jiaxiong Wu; Yi Yang; Bing Song; Zhiwei Li (Ocean Engineering, 2026)

Co-contamination of hybrid microplastics and PFOA/GenX alters rhizosphere bacterial–fungal communities and root performance of Eichhornia crassipes - Zu-lin Hua; Zi-wei Chen; Ye-bing Shi; Li Gu (Journal of Hazardous Materials, 2026)

Core-shell biochar-zeolite fertilizer with starch coating: Boosting nutrient use in saline-alkaline rice soils via smart drone delivery & economic assessment - Chang Dong; Aosheng Bai; Xu Zhao; Yang Cheng; Qinglong Chen; Phoutthasone Sibounavong; Xin-Fu Ye; Yongfu Li; Yanjiang Cai; Jie Zhu; Ruohui Lu; Bing Yu (Environmental Research, 2026)

Source-specific oxidative potential and health risks of PM2.5-bound toxic elements in Xiamen Port: Insights into ship emission contributions - Si-Min Zhao; Qi-Yu Miao; Jia-Min Li; Xin-Ye Wu; Bing-Qi Jiang; Li-Xiong He; Yi-Jing Liu; Zhi Huang; Chung-Shin Yuan; Shui-Ping Wu (Atmospheric Pollution Research, 2026)

Activation-induced cytidine deaminase (AID) suppresses the activity of HBV EnhII/CP by downregulating FANCE expression - Weiping Zhou; Biao Yang; Ye Sun; Yuxin Bai; Xuanhe Fu; Bing Nie; Ying Li; Xing Tian; Zhongjia Jiang; Guangyan Liu (Virus Genes, 2026)

Plant-derived CTLA-4-targeting miR152 via lipid nanoparticles potentiates doxorubicin efficacy in breast cancer immunochemotherapy - Hanyi Ye; Wei Jin; Yifan Feng; Ze Wu; Shuhui Sun; Mengyao Cui; Shun Lv; Bing Jin; Chang Liu; Siming Wang; Ying Li; Zhengqi Dong (Science China Life Sciences, 2026)

Metabolomic profiling and functional regulation of rabbit meat: from pre-harvest to post-mortem changes - Naqash Goswami; Ifeanyi S. Ahamba; Jiamin Zhai; Jia Haofan; Li Zhen; Wu Jie; Lionel Kinkpe; Ye Xianyang; Guohua Song; Ali Mujtaba Shah; Pavan Kumar; Xianggui Dong; et al. (Food Chemistry, 2026)

Influence of curing temperature on the carbonation products and mechanical performance of reactivated cementitious materials - Ye Li; Yutong Ju; En-hua Yang; Bing Zhang; Tiejun Liu (Waste Management, 2026)

Metabolomic and transcriptomic analysis reveals the impact of fruit bagging on cork spot disorder in ‘Akizuki’ pear fruit - Xueqian Wang; Lingxia Chen; Zixiao Wu; Jie Deng; Jintong Hu; Wei Wu; Bing Jia; Lun Liu; Xiaomei Tang; Li Liu; Zhenfeng Ye; Wei Heng (Postharvest Biology and Technology, 2026)

Long-term effects of two species feeding on polystyrene (PS) and polyethylene (PE): Differences in growth and development, and changes in protein and lipid metabolism - Conghao Liu; Jiaxin Wu; Kangni Wang; Xu Gao; Jiayi Li; Jiaqi Zhang; Xinrui Chen; Jing Li; Tong Ye; Shan Wang; Bing Zhang (Journal of Environmental Chemical Engineering, 2026)

Multi-model estimation reveals substantial but decreasing wheat yield gaps in China during the last four decades - Zi Ye; Yuan Cao; Senthold Asseng; Bing Liu; Li Jiang; Bruno Basso; Xiaolei Qiu; Liang Tang; Weixing Cao; Leilei Liu; Yan Zhu (European Journal of Agronomy, 2026)

Holocene coastal sedimentary evolution of the southern Taihu Plain, East China - Yuhai Wang; Bing Song; Deke Xu; Yulong Niu; Peng Qian; Ting Chen; Ye Yang; Feng Wang; Jun Kuang; Hao Li; Chang Li; Jiatong Lü; et al. (Marine Micropaleontology, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Flow-induced shear enhancement of dynamic lubrication surfaces for combating complex biofouling in biliary stents - Jiaxin Liu; Junchang Guo; Wei Liu; Han Yao; Linjie Guo; Yuan Gao; Bingyang Lu; Luohuizi Li; Huali Yu; Jing Luo; Liansong Ye; Xu Deng; et al. (Chemical Engineering Journal, 2026)

Simultaneous detection of Mycobacterium tuberculosis complex and rifampin/isoniazid resistance with sanity 2.0 MTBC-MDR: a moderate-complexity automated NAAT - Xichao Ou; Bing Zhao; Hui Xia; Xundi Bao; Dongfang Xu; Qi Ma; Ye Xu; Jingjing Li; Wenzhi Shi; Feina Li; Yajie Guo; Ruida Xing; et al. (World Journal of Microbiology and Biotechnology, 2026)

A machine learning framework bridging heavy metal contamination and human health risks in agricultural soils of the Yangtze River Delta (2001–2030) - Luming Xiao; Pu Feng; Yuehong Liang; Bing Xia; Yang Ye; Huijun Liu; Wenlu Zhao; Zhiheng Li; Kaiming Cheng; Jie Chen (Journal of Hazardous Materials, 2026)

ASSR-mediated sludge yield reduction couples deterministic enrichment of Nitrospira with metabolic resource partitioning - Huanzhong Deng; Junling Yang; Ruohong Li; Kewen Li; Hui Lu; Bing Lin; Xingquan Xu; Jiajun Liao; Congrong Ye; Jie Deng; Bo Wu; Lianpeng Sun (Water Research, 2026)

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

Submerge-emerge alternation regulates per(poly)fluoroalkyl substance fate in emergent plants: Insights from growth, physiology, and metabolomics - Ye-bing Shi; Zu-lin Hua; Zi-wei Chen; Xiao-qing Li; Li Gu (Aquatic Toxicology, 2026)

Effect of pH shift on the formation and structural properties of Inca peanut albumin–Dendrobium officinale polysaccharide composite gels - Bin Han; Honglang Liu; Lixuan Chen; QianJun Ye; Pan Li; Bing Du; Lu Li (Food Chemistry, 2026)

Bidirectionally regulated catalytic performance of Hemin/oCNT based aptasensor via salt-induced charge screening for smartphone-assisted colorimetric detection of ATP - Tingsong Ye; Rongwei Cui; Xin Zhou; Yingying Huang; Xin Li; Sami Ramadan; Bing Li; Lizhou Xu; Danyang Li (Chemical Engineering Journal, 2026)

Green and efficient alkaline DES pretreatment for full-component fractionation of reed biomass: Hemicelluloses, uncondensed lignin and easily digestible cellulose - Haozhi Zhang; Qian Sun; Yi-Bing Liu; Cheng-Ye Ma; Jia-Long Wen; Zhenglong Li; Tong-Qi Yuan (Chemical Engineering Journal, 2026)

Whether the hybridization of polystyrene, polyethylene, and polypropylene microplastics impacts aquatic carbon leakage from water hyacinth: A case study considering per(poly)fluorocarboxylicacid cocontamination - Zi-wei Chen; Zu-lin Hua; Ye-bing Shi; Li Gu; Chun Wang (Journal of Environmental Chemical Engineering, 2025)

Protonated pentaethylenehexamine-functionalized hydrochar for adsorption of anionic pharmaceuticals and controlled-release of pesticides - Lei Cui; Kun Ye; Shu-Han Chai; Qian Zhang; Bing Li (Chemical Engineering Journal, 2025)

Engineering Janus composite electrolytes with catalytic yolk-shell manganese oxide@C nanorods and polyimide frameworks for durable lithium-sulfur batteries - Yun-Sheng Ye; Boy-Yan Xie; Wei-Ming Huang; Jing-Yu Li; Mohamed Gamal Mohamed; Bing-Joe Hwang; Shiao-Wei Kuo (Chemical Engineering Journal, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Towards probabilistic interpretations for the deterministic magnetic inversion: A case study of borate deposits of Liaoning province, Northeast China - Ce Yang; Changwei Qi; Bing Liu; Xiujing Tang; Guitao Sun; Xiaolong Wei; Yingqiang Yu; Baochun Li; Gaofeng Ye; Ji’en Dong (Applied Geophysics, 2025)

Backarc rifting of Nanpanjiang basin: Evidence from the mineral geochemistry and Sr–Nd–Pb–Hf isotopes of Triassic High-Mg andesites in Funing area, South China - Zhenglin Li; Xijun Liu; Yu Shi; Jifeng Xu; Bing Zhao; Baohua Wang; Xiao Liu; Ye Yao; Ying Liang (Lithos, 2025)

Propranolol-loaded multifunctional hydrogel enhances the repair of infected bone defects via sympathetic microenvironment remodelling - Wenzhe Sun; Lian Zeng; Pengqing Zhang; Hongwei Lu; Bing Ye; Yizhou Wan; Yi Xu; Jialin Yu; Tingfang Sun; Yanzhen Qu; Bin Wu; Xiaohan Li; et al. (Chemical Engineering Journal, 2025)

Machine learning and causal inference for disentangling air pollution reduction during the Asian Games in megacity Hangzhou - Fan Zhang; Renchang Yan; Xianman Ye; Luolan Fei; Yaofu Zhu; Xiyao Chen; Shupeng Zhu; Bing Qi; Da Xu; Weijun Li (Environmental Pollution, 2025)

Sponge-like PNIPAM/Fe3O4/PPy composite hydrogel actuator with rapid response, self-sensing and multiple manipulating manners for complex application scenarios - Xingchen Cui; Bing Zhang; Pingzhi Shao; Linlin Li; Shunsheng Ye; Fuqiang Fan; Yu Fu; Fanbao Meng; Tieqiang Wang (Chemical Engineering Journal, 2025)

Boosting lattice oxygen reactivity via WO coordination and electronic structure modulation in NiFe-LDH electrocatalysts - Yawen Xu; Ye Li; Yizhi Du; Jinlong Zhang; Siyi Li; Chao Zhang; Xiaoli Ren; Zhiqiang Xu; Bing Xue; Fangfei Li (Chemical Engineering Journal, 2025)

Heterojunction and homojunction engineering on multi-shelled confinement structure for CO2 photoreduction to CH4 - Xiaohan Yang; Ruixin Yang; Xuanzhao Lu; Yue Cao; Peng Ye; Long Zhang; Kai Li; Zhe Li; Yujing Jiang; Juan Liu; Yuanzhen Zhou; Zafer Eroglu; et al. (Chemical Engineering Journal, 2025)

Biochar alleviates adverse effects of polystyrene microplastics on anaerobic digestion performance of food waste and antibiotic resistance gene propagation - Feng Wang; Ye Li; Linjie Zhang; Yinglong Su; Yan Zhang; Seungkwan Hong; Min Zhan; Bing Xie (Bioresource Technology, 2025)

Nrf2 signaling pathway activation through Keap1-dependent and -independent mechanisms in response to acute benzo[a]pyrene exposure in Mytilus coruscus - Yu Chen; Li Zhu; Yingying Ye; Mingshan Song; Weifeng Wang; Bing Shen; Baoying Guo; Xiaojun Yan; Pengzhi Qi (Aquatic Toxicology, 2025)

Undescribed isoprenoids obtained from Dictamnus dasycarpus Turcz and their cytotoxic activities - Sun Ye; Si-Yi Wang; Yang Xu; Jia-Tong Wu; Juan Pan; Zhi-Chao Hao; Wei Guan; Zhen-Peng Xu; Yuan-Yuan Zhou; Shao-Wa Lv; Qing-Shan Chen; Li-Li Zhang; et al. (Natural Product Research, 2025)

The emerging threat of hybrid microplastics: Impacts on per(poly)fluoroalkyl substance bioaccumulation and phytotoxicity in floating macrophytes - Zi-wei Chen; Zu-lin Hua; Ye-bing Shi; Li Gu; Fu-zhu Ye; Jia-yun Chen; Peng Guo (Journal of Hazardous Materials, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Unlocking interfacial electron transfer in biophotoelectrochemical processes: Role of extracellular polymeric substances in aquatic environments - Andong Hu; Bing Li; Shang Yang; Chaohui Yang; Jie Ye; Yuefei Huang; Shungui Zhou; Guangqian Wang (Water Research, 2025)

Bridging the mercury exposure threshold: Development and application of whole-cell biosensors incorporating biotransformation pathways - Xue-ying Liu; Yan Guo; Wen-qi Zhang; Jiao Bai; Bing-chan Ma; Li-ting Zhou; Chang-ye Hui (Environmental Research, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

The biodegradation pathway of HBCDs in the enriched microbial community - Bing Zhang; Wenqi Luo; Yongjin Liu; Haonan Chen; Tiantian Pan; Baole Wang; Keyan Li; Huaqing Jia; Shirou Zhou; Shanshan Meng; Xueying Ye; Tao Peng; et al. (International Biodeterioration & Biodegradation, 2025)

Structured ion rectifiers constructed by electrochemical in situ nano-self-assemble technique using ultrathin dickite nanosheets for aqueous zinc-ion batteries - Ye Li; Fangfei Li; Jing Wen; Haiyan Wang; Yawen Xu; Kuo Yang; Zhuo Zhang; Bing Xue (Chemical Engineering Journal, 2025)

Vertically oriented micron-thick perovskite film enables efficient and stable inverted perovskite solar cells - Bing-Hao Lv; Yong-Chun Ye; Jun-Gan Wang; Liu-Jiang Zhang; Yu-Hang Zhang; Ming-Li Zheng; Xian-Min Chen; Hui-Wei Du; Jie Yang; Xin-Yu Zhang; Meng-Lei Xu; Qiu-Feng Ye; et al. (Chemical Engineering Journal, 2025)

Green synthesis of polysaccharide-based Ag@AgCl photoactive porous hydrogel spheres for enhanced visible light photocatalytic degradation of organic pollutants - Yutong Wen; Na Qi; Ye Zhang; Zhiqi Li; Bing Fan; Meng Zhang; Ying Li (Carbohydrate Polymers, 2025)

Hydrothermal signatures in sediments along the South Mid-Atlantic Ridge from 18°S to 22°S: implications for potential hydrothermal fields - Peng Yang; Chuanshun Li; Jihua Liu; Baoju Yang; Jun Ye; Bing Li; Yuan Dang; Dewen Du (Journal of Oceanology and Limnology, 2025)

Biogeochemical sulfide mineralization in the volcanic-hosted Tongguan hydrothermal field, southern Mid-Atlantic Ridge - Bing Li; Xuefa Shi; Chuanshun Li; Sai Wang; Jun Ye; Quanshu Yan; Yuan Dang; Xisheng Fang (Frontiers in Marine Science, 2025)
Biogeochemical mineralization is increasingly recognized as a significant factor in the formation of submarine hydrothermal sulfide deposits. While several mechanisms by which hydrothermal organisms may facilitate metal deposition have been documented in many seafloor hydrothermal deposits, the potential involvement of biogenic processes in the mineralization of hydrothermal deposits in the southern Mid-Atlantic Ridge (SMAR) has been largely overlooked until now. In this study, we investigate sulfide chimney sample from the volcanic-hosted Tongguan hydrothermal field on the SMAR and present several lines of evidence for biogeochemical mineralization. Mineralogical analysis infers four types of biogenic pyrite and chalcopyrite structures: macrobiotic-related tube structures, microbial-related quasi-stromatolite, quasi-oncolite and globular structures. These biogenic structures exhibit selective enrichment of elements such as Mn, Pb, and Cu in biogenic pyrite compared to abiotic pyrite. In-situ sulfur isotope studies indicate that biogenic minerals possess lower δ 34 S values than abiotic minerals. We identified three biomineralization mechanisms: an “active” mineralization process mediated by macro-organism, a “passive” mineralization process associated with microbial mats, and a microbial assimilatory sulfate reduction process. Our research suggests that the role of biogenic processes in SMAR hydrothermal mineralization should be given further consideration.

Distribution of microbial taxa and genes degrading halogenated organic pollutants in the mangroves - Fei Yu; Yuyang Li; Shanshan Meng; Bing Zhang; Yongjin Liu; Wenqi Luo; Zhihui Qian; Wei Xie; Xueying Ye; Amit Pratush; Tao Peng; Hui Wang; et al. (Journal of Hazardous Materials, 2025)

Lactic acid/tartaric acid-maltitol antibacterial activity against spoilage bacteria and prevention of yellowing and wilting in spinach and oilseed rape - Dengyi Ye; Jing Ren; Yanan Zhang; Xiyu Wang; Jiali Guo; Bing Li; Quanliang Li; Yanjun Chen; Ping Chen; Biying Zhang (Food Chemistry, 2025)

Deleted in malignant brain tumors 1 (DMBT1) gene relate to immune priming and phagocytosis modulation in the small abalone Haliotis diversicolor - Tuo Yao; Junyuan Tan; Jie Lu; Shengli Fu; Zhilv Xie; Bing Li; Changhong Cheng; Lingtong Ye (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

High-performance dickite strengthened double-crosslinked hydrogel electrolytes for aqueous zinc-ion batteries - Ziwen Ma; Ye Li; Zhi Qu; Zhonghua Ma; Kuo Yang; Fangfei Li; Bing Xue (Applied Clay Science, 2025)

Design of Palygorskite–based Quasi-solid-state electrolyte and Construction of Stable Electrode/Electrolyte Interface for High Cycling Stability Aqueous Zinc-ion Batteries - Zhuo Zhang; Haiyan Wang; Kuo Yang; Feifei Zhang; Ye Li; Bing Xue; Xiaopeng Gu (Applied Clay Science, 2025)

Cell-free hemoglobin released from hemolysis induces programmed cell death through iron overload and oxidative stress in grass carp (Ctenopharyngodon idella) - Jialing Song; Ningjing Li; Yan Yang; Bing Chen; Jiaxiang Hu; Ye Tian; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2025)

Hemolysis-associated release of hemoglobin induces mitochondrial oxidative phosphorylation (OXPHOS) disturbance and aggravates cell oxidative damage in grass carp (Ctenopharyngodon idella) - Yan Yang; Ningjing Li; Jialing Song; Ye Tian; Bing Chen; Jiangtao Li; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2025)

Redox-copolymer-enhanced electrochemical catalysis membrane for efficient water decontamination - Zhen Qiu; Cheng Chen; Xin Zeng; Guanda Shen; Qisheng Ye; Hailu Fu; Yongfu Li; Bing Yu (Chemical Engineering Journal, 2025)

Application of 18β-glycyrrhetinic acid in the structural modification of natural products: a review - Wan-Xin Li; Ye-Fang Lu; Fei Wang; Bing Ai; Sheng-Bo Jin; Siqi Li; Guang-Hua Xu; Cheng-Hua Jin (Molecular Diversity, 2025)

Efficient removal of levofloxacin by FeCo2O4@C-REC activated peroxymonosulfate: Performance and mechanism - Bai-Hang Zhao; Bao-Yu Zhang; Bing-Lin Zhang; Jing Zhang; Chun Wang; Ye Li (Journal of Water Process Engineering, 2025)

Effects of FRP fiber orientations on four-point bending behaviour of FRP-concrete-steel tubular beams: Experimental study and modeling - Bing Zhang; Chong Zhou; Sumei Zhang; Yutao Peng; Ye Li (Engineering Structures, 2025)

Submerge-emerge alternation promotes sediment per- and polyfluoroalkyl substance (PFAS) release and bioaccumulation - Ye-bing Shi; Zu-lin Hua; Xiao-qing Li; Song-he Zhang; Jian-long Liu (Science of The Total Environment, 2024)

Dickite nanolayers for ultrathin anode coatings in highly stable zinc-ion batteries - Ye Li; Fangfei Li; Kuo Yang; Haiyan Wang; Zhuo Zhang; Bing Xue (Applied Clay Science, 2024)

Fusarium graminearum spores disrupt gut microbiota and metabolome via the lung-gut axis in mice - Yuting Wang; Bing Wu; Xingxing Gao; Jinyou Li; Jin Yang; Yongli Ye; Jiadi Sun; Lina Sheng; Song Gao; Yinzhi Zhang; Jian Ji; Xiulan Sun (Journal of Hazardous Materials, 2024)

Photoelectrochemical methane production achieved energy recovery from wastewater with low organic concentration - Andong Hu; Tao Fu; Jie Ye; Yuefei Huang; Shungui Zhou; Bing Li; Guangqian Wang (Chemical Engineering Journal, 2024)

A Clay-Based Quasi-Solid-State electrolyte with high cation selective channels for High-Performance aqueous Zinc-Ion batteries - Haiyan Wang; Zhuo Zhang; Ye Li; Feifei Zhang; Kuo Yang; Bing Xue (Chemical Engineering Journal, 2024)

The effects of top-down political inspection on bottom-up public complaints in China - Jinchi Dong; Miaomiao Liu; Wei Zhang; Hongqiang Jiang; Jinnan Wang; Bing Zhang; Ye Shu; Li Sun; Jun Bi (Journal of Cleaner Production, 2024)

Timescale dependent homogeneous assembly of lipid-polymer hybrid nanoparticles in laminar mixing for enhanced lung cancer treatment - ShiXin Li; Bing Yang; Liang Ye; ShuQi Hu; BenHong Li; Yanjun Yang; XiaoBin Jia; Liang Feng; ZhiWei Xiong (Chemical Engineering Journal, 2024)

Magma degassing of ore-metals into submarine hydrothermal systems: a case study from the Xunmei hydrothermal field, South Mid-Atlantic Ridge - Sai Wang; Chuanshun Li; Bing Li; Yili Guan; Yuan Dang; Jun Ye; Xuefa Shi; Yongqiang Yang (Contributions to Mineralogy and Petrology, 2024)

Causal prior-embedded physics-informed neural networks and a case study on metformin transport in porous media - Qiao Kang; Baiyu Zhang; Yiqi Cao; Xing Song; Xudong Ye; Xixi Li; Hongjing Wu; Yuanzhu Chen; Bing Chen (Water Research, 2024)

An oceanic core complex and its associated weathered hydrothermal deposit on a ridge-transform intersection zone at 23°S, Southern Mid-Atlantic Ridge - Bing Li; Jixin Wang; Chuanshun Li; Sai Wang; Lei Fan; Jun Ye; Yuan Dang; Quanshu Yan; Xuefa Shi (Marine Geology, 2024)

Ultrastable fluorinated copolypeptide nanodroplets of loaded mixed liquids with low vaporization threshold - Xianjun Ye; Bing Shao; Xianxian Jiang; Juan Li; Xiao Liu; Xia Chen; Yayun Cui; Chaoxue Zhang; Jie Cen; Nianan He (Chemical Engineering Journal, 2024)

Treating waste with waste: adsorption behavior and mechanism of phosphate in water by modified phosphogypsum biochar - Li-li Shan; Ruo-shan Wang; Hai-tao Lai; Ze-bing Zhu; Yu Chen; Zhu-ye Ni; Chang-long Pang; Qiu-zhuo Zhang (Environmental Science and Pollution Research, 2024)

Mutually reinforced cancer treatment based on phototherapy combined with ferroptosis - Guan-Hong Chen; Lei Gan; Li-Yuan Tian; Bin-Xin Huang; Qiang Xiao; Yi-Jing Zhang; Mei-Tian Xiao; Bing-De Zheng; Jing Ye (Chemical Engineering Journal, 2024)

Syn- and post-collisional mafic igneous rocks from the East Kunlun Orogenic Belt: Implications for recycling of subducting continental crust during the Silurian-Devonian - Li-Tao Ma; Guo-Chao Sun; Li-Qun Dai; Zi-Fu Zhao; Ye-Dan Hu; Qing-Cheng Yang; Lei Qin; Bing Gong (Lithos, 2024)

Largely enhanced Piezoelectric-Fenton capability in rationally designed PVDF/Fe2O3 flexible porous film - Xin Yang; Fei Ye; Zeyu Li; Xiaoling Liu; Jiaying Chu; Bing Xie; Liudi Ji; Peng Hu; Juntao Wang; Jifu Du; Xiaoming Zhu (Journal of Environmental Chemical Engineering, 2024)

Near-infrared laser induced direct ignition of 4,4′,5,5′-tetranitro-1H,1′H-[2,2′-biimidazole]-1,1′-diamine by constructing diverse crystal structures - Ping Ye; Weimiao Wang; Xiaodong Li; Zhiqiang Qiao; Yirui Lu; Bing Huang; Liangfei Bai; Liang Chen; Xiaoqing Tu; Rui Li; Guangcheng Yang; Guoqing Lv (Chemical Engineering Journal, 2024)

Synergic regulation of crystalline phase, composition and morphology of SAPO-34 via metal assistance and in situ etching strategy - Xiaosi Zhang; Miao Yang; Dong Fan; Ye Wang; Caiyi Lou; Haocheng Hu; Bing Li; Peng Tian; Zhongmin Liu (Chemical Engineering Journal, 2024)

Effects of exercise on muscle fiber conversion, muscle development and meat quality of Sunit sheep - Lin Su; Congying Zhao; Bing Sun; Lu Dou; Chenlei Wang; Zhihao Yang; Tianle Li; Ye Jin (Meat Science, 2024)

Biotransformation of HBCDs by the microbial communities enriched from mangrove sediments - Fei Yu; Bing Zhang; Yongjin Liu; Wenqi Luo; Haonan Chen; Jun’na Gao; Xueying Ye; Jin Li; Qingyi Xie; Tao Peng; Hui Wang; Tongwang Huang; et al. (Journal of Hazardous Materials, 2024)

A multi-criteria simulation-optimization coupling approach for effective emergency response in marine oil spill accidents - Xudong Ye; Baiyu Zhang; Kenneth Lee; Rune Storesund; Xing Song; Qiao Kang; Pu Li; Bing Chen (Journal of Hazardous Materials, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

Social parasitism behavior between two species of edible wasps in China - Cheng-Ye Wang; Hao-Yu Chen; Bing-Qing Fang; Pan-Li Yang; Zhao He; Long Sun; Jin Gan; Min Zhao; Ying Feng (Journal of Ethology, 2024)

Humic substances mediated superior photochemical pollutant conversion on defective TiO2 in environmentally relevant matrices: The key roles of oxygen vacancy in surface interactions, oxidant activation and radical generation - Song Hu; Lyumeng Ye; Bing-Jie Tian; Jia-Ying Li; Ai-Yong Zhang; Lu Zhao; Chi Zhang; Chu Jiang; Zhi-Xian Lin; Wei Da; Qi-Xin Wei (Science of The Total Environment, 2024)

Identification and evaluation of new specific targets based pan-genome analysis for rapid detection of Burkholderia gladioli pathovar cocovenenans and Burkholderia gladioli in foods - Bing Li; Wei Chen; Meiping Zhao; Chengsi Li; Bao Gao; Meiqing Deng; Qingping Wu; Qihui Gu; Youxiong Zhang; Xianhu Wei; Jumei Zhang; Qinghua Ye (Food Control, 2024)

Distribution Characteristics, Source Analysis of Heavy Metal(oid)s, and Ecological and Health Risk Assessment around Shale Gas Extraction Platform in Sichuan, China - Bing Wang; Kefeng Li; Hong Ye; Chunyang Gao; Wenhui Jin; Guilin Xie (Water, Air, & Soil Pollution, 2024)

Self-adjuvant Astragalus polysaccharide-based nanovaccines for enhanced tumor immunotherapy: a novel delivery system candidate for tumor vaccines - Nan Li; Yun Zhang; Miaomiao Han; Tian Liu; Jinjia Wu; Yingxia Xiong; Yikai Fan; Fan Ye; Bing Jin; Yinghua Zhang; Guibo Sun; Xiaobo Sun; et al. (Science China Life Sciences, 2024)

Goethite adaptation prompts alterations in antibiotic susceptibility and suppresses development of antibiotic resistance in bacteria - Yongtao Xu; Haiqing Wang; Sheng Ye; Zhenda Liang; Zhiquan Chen; Xiaohong Wang; Li Zhou; Bing Yan (Science of The Total Environment, 2024)

Horizontal transfer potential of antibiotic resistance genes in wastewater treatment plants unraveled by microfluidic-based mini-metagenomics - Jiachen Ma; Haohao Sun; Bing Li; Bing Wu; Xuxiang Zhang; Lin Ye (Journal of Hazardous Materials, 2024)

Clinical and genetic architecture of a large cohort with auditory neuropathy - Hongyang Wang; Liping Guan; Xiaonan Wu; Jing Guan; Jin Li; Nan Li; Kaili Wu; Ya Gao; Dan Bing; Jianguo Zhang; Lan Lan; Tao Shi; et al. (Human Genetics, 2024)
Auditory neuropathy (AN) is a unique type of language developmental disorder, with no precise rate of genetic contribution that has been deciphered in a large cohort. In a retrospective cohort of 311 patients with AN, pathogenic and likely pathogenic variants of 23 genes were identified in 98 patients (31.5% in 311 patients), and 14 genes were mutated in two or more patients. Among subgroups of patients with AN, the prevalence of pathogenic and likely pathogenic variants was 54.4% and 56.2% in trios and families, while 22.9% in the cases with proband-only; 45.7% and 25.6% in the infant and non-infant group; and 33.7% and 0% in the bilateral and unilateral AN cases. Most of the OTOF gene (96.6%, 28/29) could only be identified in the infant group, while the AIFM1 gene could only be identified in the non-infant group; other genes such as ATP1A3 and OPA1 were identified in both infant and non-infant groups. In conclusion, genes distribution of AN, with the most common genes being OTOF and AIFM1 , is totally different from other sensorineural hearing loss. The subgroups with different onset ages showed different genetic spectrums, so did bilateral and unilateral groups and sporadic and familial or trio groups.

Mechanistic insights into the effects of diuron exposure on Alexandrium pacificum - Dan Huang; Cai-Qin Cheng; Jiang-Bing Qiu; Yun Huang; Hao-Yun Zhang; Zhen-Hao Xu; Si-Wei Wu; Yi-Tong Huang; Jian Chen; Li-Gong Zou; Wei-Dong Yang; Xiao-Fei Zheng; et al. (Water Research, 2024)

Integrated surrogate framework for reactive transport simulation of uranium in situ leaching with generative models - Wen-gui Ji; Yue Luo; Bing Wang; Xun Li; Jin-hui Liu; Yan-hong Zhang; Da-ye Liang (Journal of Hydrology, 2024)

A joint parcellation and boundary network with multi-rate-shared dilated graph attention for cortical surface parcellation - Siqi Liu; Hailiang Ye; Bing Yang; Ming Li; Feilong Cao (Medical & Biological Engineering & Computing, 2024)

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Mechanism of Cr(VI) removal by efficient Cr(VI)-resistant Bacillus mobilis CR3 - Yubo Ye; Ruixia Hao; Bing Shan; Junman Zhang; Jiani Li; Anhuai Lu (World Journal of Microbiology and Biotechnology, 2024)

Metallogenetic process of Xunmei hydrothermal field (26°S), South Mid-Atlantic Ridge: Constraints from in-situ sulfur isotope and trace elements of sulfides - Yuan Dang; Chuanshun Li; Xuefa Shi; Sai Wang; Jun Ye; Bing Li; Yue Yang; Qiukui Zhao; Yili Guan; Jingwen Mao (Marine Geology, 2023)

Dopaminergic and serotoninergic neurotoxicity of lanthanide phosphate (TbPO4) in developing zebrafish - Siying Chen; Xiaohong Wang; Xiaolin Ye; Yingju Qin; Haiqing Wang; Zhenda Liang; Lishan Zhu; Li Zhou; Christopher J. Martyniuk; Bing Yan (Chemosphere, 2023)

Machine learning–based optimal design of the in-situ leaching process parameter (ISLPP) for the acid in-situ leaching of uranium - Bing Wang; Yue Luo; Jia-zhong Qian; Jin-hui Liu; Xun Li; Yan-hong Zhang; Qian-qian Chen; Li-yao Li; Da-ye Liang; Jian Huang (Journal of Hydrology, 2023)

Chromium isotope variations in garnet-facies mantle rocks and their minerals: Implications for Cr isotope behavior in high-temperature processes - Ji Shen; Zhiwei Zuo; Bing Yang; Dmitri A. Ionov; Wang-Ye Li; Liping Qin (Geochimica et Cosmochimica Acta, 2023)

Engineering of cyanine-based nanoplatform with tunable response toward reactive species for ratiometric NIR-II fluorescent imaging in mice - Yuan Ma; Liuhui Liu; Zhifei Ye; Li Xu; Yuhang Li; Sulai Liu; Guosheng Song; Xiao-Bing Zhang (Science Bulletin, 2023)

Sulfur-decorated Fe/C composite synthesized from MIL-88A(Fe) for peroxymonosulfate activation towards tetracycline degradation: Multiple active sites and non-radical pathway dominated mechanism - Jin Qian; Yichu Zhang; Zhijie Chen; Ran Yu; Yin Ye; Rui Ma; Kailong Li; Lingzhen Wang; Dongqi Wang; Bing-Jie Ni (Journal of Environmental Management, 2023)

Exploring the mechanism of enhanced Cr(VI) removal by Lysinibacillus cavernae microcapsules loaded with synthetic nano-hydroxyapatite - Bing Shan; Ruixia Hao; Junman Zhang; Yubo Ye; Jiani Li; Hui Xu; Anhuai Lu (Environmental Science and Pollution Research, 2023)

Punicalagin alleviates the hyperproliferation of keratinocytes in psoriasis through inhibiting SKP2 expression - Lipeng Tang; Bowen Zhang; Guanzhuo Li; Ying Zhu; Bing Feng; Zuqing Su; Wenhui Han; Huilin Huang; Qiuping Li; Maojie Wang; Yuchao Chen; Huazhen Liu; et al. (Journal of Natural Medicines, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Revisiting China's domestic greenhouse gas emission from wastewater treatment: A quantitative process life-cycle assessment - Dengting Guo; Bing Li; Wei Yu; Jing-Cheng Han; Yang Zhou; Zhilong Ye; Xiaofeng Wu; Brent Young; Yuefei Huang (Science of The Total Environment, 2023)

Identification of 14 glutathione S-transferase genes from Lasioderma serricorne and characterization of LsGSTe1 involved in lambda-cyhalothrin detoxification - Xi-Ya Liu; Hui-Mei Sun; Yi-Hong Luo; Mao-Ye Li; Hai-Bing Liu; Su Liu (Pesticide Biochemistry and Physiology, 2023)

Quantitative assessment of the shoreline protection performance of geotextile sandbags at an in-situ coastal experimental station - Yongqing Li; Zai-Jin You; Ye Ma; Bing Ren (Geotextiles and Geomembranes, 2023)

A review of the migration mechanism of antibiotics during struvite recovery from wastewater - Degui Gao; Bing Li; Xuewei Huang; Xiaoning Liu; Ruili Li; Zhilong Ye; Xiaofeng Wu; Yuefei Huang; Guangqian Wang (Chemical Engineering Journal, 2023)

Mutational investigation of 17 causative genes in a cohort of 113 families with nonsyndromic early-onset high myopia in northwestern China - Min Ye; Ya Ma; Yi-Xuan Qin; Bo Cai; Li-mei Ma; Zhen Ma; Yang Liu; Zi-Bing Jin; Wen-Juan Zhuang (Molecular Genetics and Genomics, 2023)

RETRACTED: Determining the spatial non-stationarity underlying social and natural environment in thyroid cancer in China - Xiyu Zhang; Yongqiang Lai; Xiaodan Bai; Bing Wu; Wenjing Xiang; Chenxi Zhang; Guihong Geng; Wenqing Miao; Qi Xia; Qunhong Wu; Huiying Yang; Yanjie Wang; et al. (Science of The Total Environment, 2023)

New approaches to modeling the critical refreezing length of a Philberth melt probe for ice sheet exploration - Yazhou Li; Pavel G. Talalay; Xiaopeng Fan; Bing Li; Liang Xu; Yuting Ye; Yue Wang (Polar Science, 2023)

Applying struvite as a N-fertilizer to mitigate N2O emissions in agriculture: Feasibility and mechanism - Lei Wang; Chengsong Ye; Bing Gao; Xiaojun Wang; Yaying Li; Kai Ding; Hu Li; Kexin Ren; Shaohua Chen; Wei Wang; Xin Ye (Journal of Environmental Management, 2023)

Enhanced anaerobic digestion performance of food waste by zero-valent iron and iron oxides nanoparticles: Comparative analyses of microbial community and metabolism - Panliang Wang; Xunan Li; Ye Li; Yinglong Su; Dong Wu; Bing Xie (Bioresource Technology, 2023)

Solvent-free oxidation of toluene to benzaldehyde using electron-rich Au clusters confined in Silicalite-1 - He Huang; Huahua Fan; Yuzhen Ge; Wanyue Ye; Yingcen Liu; Caicheng Song; Hua Lin; Xiaotong Zhang; Bing Li; Xiaowa Nie; Shufen Zhang; Rongwen Lu (Chemical Engineering Journal, 2023)

Microbial remediation mechanisms and applications for lead-contaminated environments - Bing Shan; Ruixia Hao; Junman Zhang; Jiani Li; Yubo Ye; Anhuai Lu (World Journal of Microbiology and Biotechnology, 2023)

Evaluation of the mid- and long-term effects of a private car driving–restriction policy under the carbon emission peak target - Zhen Chen; Xiangyang Ye; Bing Li; Shuwei Jia (Environmental Science and Pollution Research, 2023)

SnoRNP is essential for thermospermine-mediated development in Arabidopsis thaliana - Xilong Li; Zongyun Yan; Meiling Zhang; Jiayin Wang; Peiyong Xin; Shujing Cheng; Liquan Kou; Xiaoting Zhang; Songlin Wu; Jinfang Chu; Chengqi Yi; Keqiong Ye; et al. (Science China Life Sciences, 2023)

Correction to: Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2023)

CuO decorated vacancy-rich CeO2 nanopencils for highly efficient catalytic NO reduction by CO at low temperature - Fei Wang; Zairan Yu; Shuai Zhai; Yuanyuan Li; Yang Xu; Yuyang Ye; Xuejiao Wei; Jie Xu; Bing Xue (Environmental Science and Pollution Research, 2022)

STING/NF-κB/IL-6-Mediated Inflammation in Microglia Contributes to Spared Nerve Injury (SNI)-Induced Pain Initiation - Jia Sun; Ya-qun Zhou; Bing-yang Xu; Jia-yan Li; Long-qing Zhang; Dan-yang Li; Shuang Zhang; Jia-yi Wu; Shao-jie Gao; Da-wei Ye; Wei Mei (Journal of Neuroimmune Pharmacology, 2022)

Hexavalent chromium reduction and bioremediation potential of Fusarium proliferatum S4 isolated from chromium-contaminated soil - Bing Shan; Ruixia Hao; Hui Xu; Junman Zhang; Jiani Li; Yinhuang Li; Yubo Ye (Environmental Science and Pollution Research, 2022)

Modeling and simulation analysis of vehicle pollution and carbon reduction management model based on system dynamics - Zhen Chen; Bing Li; Shuwei Jia; Xiangyang Ye (Environmental Science and Pollution Research, 2022)

Long-term changes in zooplankton in the Changjiang estuary from the 1960s to 2020 - Ping Du; Wen-Jian Ye; Bang-Ping Deng; Ming Mao; Yuan-Li Zhu; Fang-Ping Cheng; Zhi-Bing Jiang; Lu Shou; Quan-Zhen Chen (Frontiers in Marine Science, 2022)
The Changjiang estuary (CJE) is a large estuary that is affected by multiple anthropogenic stressors and climate change. The long-term trend of zooplankton in the CJE is an important indicator of the ecological response to stressors. We applied the Mann–Kendall trend analysis and Pettitt test to detect the trend and breakpoints of the biomass of the large mesozooplankton (LMZ; 505–20 000 μm) in four seasons, abundance of main LMZ taxa in summer from the 1960s to 2020, and abundance of dominant species in summer from 2000 to 2020 in the CJE. Results showed that LMZ biomass increased significantly during spring and summer, and the breakpoints both occurred in the 1980s. After the breakpoint, the mean biomass increased from 142.88 to 429.42 mg/m 3 in spring and from 296.28 to 723.92 mg/m 3 in summer. After 2000, the abundance of Copepoda in summer increased by more than 10 times compared to the 1960s. Under the conditions of warming and increased dinoflagellate abundance in the CJE, the abundance of the warm-water and omnivorous small calanoid copepod Paracalanus aculeatus increased significantly. Meanwhile, the significant decrease in the abundance of the temperate brackish species Labidocera euchaeta was probably mainly related to warming. The rapid changes in LMZ biomass during the late 1980s and mid-1990s is probably the result of a combination of enhanced bottom–up support, reduced top–down pressure, and promotion of temperature. This study provides scientific evidence and insights into the adaptive management of the Changjiang Basin.

Three new sesquiterpenoid alkaloids from the roots of Tripterygium wilfordii and its cytotoxicity - Hong Liang Ye; Yan Liu; Juan Pan; Wei Guan; Yuan Liu; Xiao Mao Li; Si Yi Wang; Adnan Mohammed Algradi; Bing You Yang; Hai Xue Kuang (Natural Product Research, 2022)

Two new terpenes from the aerial parts of Clematis chinensis Osbeck - Sun Ye; Liu Yan; Yan-Ping Sun; Xiao-Mao Li; Wang Si-Yi; Juan Pan; Wei Guan; Yuan Liu; Anam Naseem; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2022)

A novel large-scale land degradation remote sensing index and its application in Three River Source Region - Ye Wen; Qiubing Wang; Bing Guo; Chao Meng; Yumei Cai; Haorun Xue; Huihui Zhao; Wenqian Zang; Cuixia Wei; Yang Yu; Yifeng Liu; Jialin Li (Earth Science Informatics, 2022)

Efficient immobilization behavior and mechanism investigation of Pb(II) by Aspergillus tubingensis - Bing Shan; Ruixia Hao; Xiyang Xu; Jiani Li; Junman Zhang; Yinhuang Li; Yubo Ye; Anhuai Lu (Biotechnology Letters, 2022)

Damaging effects of TiO2 nanoparticles on the ovarian cells of Bombyx mori - Yilong Fang; Mingli Dai; Wentao Ye; Fanchi Li; Haina Sun; Jing Wei; Bing Li (Biological Trace Element Research, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Gut dysbiosis-influence on amygdala-based functional activity in patients with end stage renal disease: a preliminary study - Li Juan Zheng; Li Lin; Jianhui Zhong; Zhihong Zhang; Yu Bing Ye; Xin Yuan Zhang; Yun Fei Wang; Han Zhang; Ya Liu; Guang Ming Lu; Dehua Gong; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Interleukin-1β in hypothalamic paraventricular nucleus mediates excitatory renal reflex - Fen Zheng; Chao Ye; Guo-Wei Wan; Bing Zhou; Ying Tong; Jian-Zhen Lei; Qi Chen; Yue-Hua Li; Yu-Ming Kang; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2020)

Noise does not equal bias in assessing the evolutionary history of the angiosperm flora of China: A response to Qian (2019) - Li‐Min Lu; Hai‐Hua Hu; Dan‐Xiao Peng; Bing Liu; Jian‐Fei Ye; Tuo Yang; Hong‐Lei Li; Miao Sun; Stephen A. Smith; Pamela S. Soltis; Douglas E. Soltis; Zhi‐Duan Chen (Journal of Biogeography, 2020)
In response to our paper on the evolutionary history of the Chinese flora, Qian suggests that certain features of the divergence time estimation employed might have led to biased conclusions in Lu et al (2018). Here, we consider Qian's specific criticisms, explore the extent of uncertainty in the data and demonstrate that (i) no systematic bias toward dates that are too young or too old is detected in Lu et al.; (ii) constraint of the crown age of angiosperms does not bias the generic ages estimated by Lu et al.; and (iii) ages derived from the Chinese regional phylogeny do not bias the conclusions reported by Lu et al. All these analyses confirm that the conclusions reported previously are robust. We argue that, like many large‐scale biodiversity analyses, sources of noise in divergence time estimation are to be expected, but these should not be confused with bias.

Characterization of Pseudomonas syringae pv. actinidiae Biovar 3 strain and cultivar tolerance to kiwifruit bacterial canker in China - Zhen-feng Ye; Peng-fei Wei; Shi-zhou Xue; Pu Liu; Bing Jia; Wei Heng; Li-wu Zhu (Journal of Plant Pathology, 2020)

Overexpression of the pear PbSPMS gene in Arabidopsis thaliana increases resistance to abiotic stress - Xianghong Jiang; Junyu Zhan; Qi Wang; Xinyi Wu; Xiaonan Chen; Bing Jia; Pu Liu; Li Liu; Zhenfeng Ye; Liwu Zhu; Wei Heng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Impacts of irrigation methods on greenhouse gas emissions/absorptions from vegetable soils - Xuhong Ye; Hongdou Liu; Xichao Zhang; Jianhui Ma; Bing Han; Wen Li; Hongtao Zou; Yulong Zhang; Xiangui Lin (Journal of Soils and Sediments, 2020)

Gaussian decomposition and component pigment spectral analysis of phytoplankton absorption spectra - Huping Ye; Bing Zhang; Xiaohan Liao; Tongji Li; Qian Shen; Fangfang Zhang; Jianhua Zhu; Junsheng Li (Journal of Oceanology and Limnology, 2019)

Contribution of Apelin-17 to Collateral Circulation Following Cerebral Ischemic Stroke - Wan Jiang; Wei Hu; Li Ye; Yanghua Tian; Ren Zhao; Juan Du; Bing Shen; Kai Wang (Translational Stroke Research, 2019)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

Docking study and antiosteoporosis effects of a dibenzylbutane lignan isolated from Litsea cubeba targeting Cathepsin K and MEK1 - Wei Peng; Hui Shen; Bing Lin; Ping Han; Changhui Li; Qiaoyan Zhang; Bingzhu Ye; Khalid Rahman; Hailiang Xin; Luping Qin; Ting Han (Medicinal Chemistry Research, 2018)

Improvement of scattering correction for in situ coastal and inland water absorption measurement using exponential fitting approach - Huping Ye; Junsheng Li; Jianhua Zhu; Qian Shen; Tongji Li; Fangfang Zhang; Huanyin Yue; Bing Zhang; Xiaohan Liao (Journal of Oceanology and Limnology, 2018)

A simple automated dynamic threshold extraction method for the classification of large water bodies from landsat-8 OLI water index images - Fangfang Zhang; Junsheng Li; Bing Zhang; Qian Shen; Huping Ye; Shenglei Wang; Zhaoyi Lu (International Journal of Remote Sensing, 2018)

Effects of environment and genotype on mercury and methylmercury accumulation in rice (Oryza sativa L.) - Lu Huang; Bing Li; Nora Fung-Yee Tam; Xun Wang; Zhihong Ye (Plant and Soil, 2018)

Correction to: Age at menarche and age at natural menopause in East Asian women: a genome-wide association study - Jiajun Shi; Ben Zhang; Ji-Yeob Choi; Yu-Tang Gao; Huaixing Li; Wei Lu; Jirong Long; Daehee Kang; Yong-Bing Xiang; Wanqing Wen; Sue K. Park; Xingwang Ye; et al. (GeroScience, 2018)

Phenolic constituents from Rheum nobile and their antioxidant activity - Ye Fei; Juan Wang; Bing Peng; Jiangnan Peng; Jing-Hong Hu; Zu-Ping Zeng; Jing Chen; Qi-En Li; Zeng-Ping Gao; Xing-Li Yan (Natural Product Research, 2017)

The effects of different irrigation regimes on nitrous oxide emissions and influencing factors in greenhouse tomato fields - Bing Han; Xuhong Ye; Wen Li; Xichao Zhang; Yulong Zhang; Xiangui Lin; Hongtao Zou (Journal of Soils and Sediments, 2017)

Identification of russet-associated microRNAs in the exocarp of a Dangshansuli pear mutant (Pyrus bretschneideri Rehd.) by high-throughput sequencing - Wei Heng; Bing Jia; Hai-na Huang; Jin-yu Yang; Zi-teng Wang; Pu Liu; Li Liu; Zhen-feng Ye; Li-wu Zhu (Tree Genetics & Genomes, 2016)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

The role of polyamines during exocarp formation in a russet mutant of ‘Dangshansuli’ pear (Pyrus bretschneideri Rehd.) - Wei Heng; Ziteng Wang; Xianghong Jiang; Bing Jia; Pu Liu; Li Liu; Zhenfeng Ye; Liwu Zhu (Plant Cell Reports, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

Inhibition of five natural products from Chinese herbs on the growth of Chattonella marina - Fei Liu; Zheng-Bing He; Hong-Ye Li; Jie-Sheng Liu; Wei-Dong Yang (Environmental Science and Pollution Research, 2016)

Endoplasmic Reticulum Stress: Relevance and Therapeutics in Central Nervous System Diseases - Hong-Yu Zhang; Zhou-guang Wang; Xiang-Hong Lu; Xiao-Xia Kong; Fen-Zan Wu; Li Lin; Xiaohua Tan; Li-Bing Ye; Jian Xiao (Molecular Neurobiology, 2015)

Radial oxygen loss has different effects on the accumulation of total mercury and methylmercury in rice - Xun Wang; Bing Li; Nora Fung-Yee Tam; Lu Huang; Xiaoli Qi; Hongbin Wang; Zhihong Ye; Mei Meng; Jianbo Shi (Plant and Soil, 2014)

Icariin-Mediated Inhibition of NF-κB Activity Enhances the In Vitro and In Vivo Antitumour Effect of 5-Fluorouracil in Colorectal Cancer - De-Bing Shi; Xin-Xiang Li; Hong-Tu Zheng; Da-Wei Li; Guo-Xiang Cai; Jun-Jie Peng; Wei-Lie Gu; Zu-Qing Guan; Ye Xu; San-Jun Cai (Cell Biochemistry and Biophysics, 2014)

Characteristics of a ridge-transform inside corner intersection and associated mafic-hosted seafloor hydrothermal field (14.0°S, Mid-Atlantic Ridge) - Bing Li; Yaomin Yang; Xuefa Shi; Jun Ye; Jingjing Gao; Aimei Zhu; Mingjuan Shao (Marine Geophysical Research, 2014)

Differentially expressed genes related to the formation of russet fruit skin in a mutant of ‘Dangshansuli’ pear (Pyrus bretchnederi Rehd.) determined by suppression subtractive hybridization - Wei Heng; Li Liu; Meng-dong Wang; Bing Jia; Pu Liu; Zhen-feng Ye; Li-wu Zhu (Euphytica, 2014)

Anchored periplasmic expression (APEx)-based bacterial display for rapid and high-throughput screening of B cell epitopes - Mo Guo; Li-Ming Xu; Bing Zhou; Jie-Chao Yin; Xian-Long Ye; Gui-Ping Ren; De-Shan Li (Biotechnology Letters, 2014)

Exploring the pattern of phenotypic and genetic polymorphism in the arsenic hyperaccumulator Pteris vittata L. (Chinese brake fern) - Bing Yang; Alessio Mengoni; Ye-Ling Huang; Xiong-Lei He; Jin-Tian Li; Bin Liao; Mi Zhou; Wen-Sheng Shu (Plant and Soil, 2013)

Antiarrhythmic effects and ionic mechanisms of allicin on myocardial injury of diabetic rats induced by streptozotocin - Wei Huang; Ye Wang; Yong-Gang Cao; Han-Ping Qi; Lei Li; Bing Bai; Yang Liu; Hong-Li Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

Polymorphisms in chicken extracellular fatty acid binding protein gene - Zhi-yuan Zhao; Li Zhang; Bing-wang Du; Ning-xian Cao; Xin-sheng Jiang; Wen-xia Tian; Shu-jun Li; Wei-wei Wu; Chang-hui Ye (Molecular Biology Reports, 2012)

Effect of long-term administration of dietary β-1,3-glucan on growth, physiological, and immune responses in Litopenaeus vannamei (Boone, 1931) - Hong-Xia Zhao; Jun-Ming Cao; An-Li Wang; Zhen-Yu Du; Chao-Xia Ye; Yan-Hua Huang; Han-Bing Lan; Ting-Ting Zhou; Guo-Li Li (Aquaculture International, 2012)

Changes of Brain Structure and Function in ADHD Children - Ming-guo Qiu; Zhang Ye; Qi-yu Li; Guang-jiu Liu; Bing Xie; Jian Wang (Brain Topography, 2011)